Experimental investigation and introduction of a similarity parameter for characterizing the heat and mass transfer in polymer desiccant wheels - Kang, Hyungmook; Lee, Dae-Young (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
The desiccant wheels made of a polymer desiccant were investigated at a low regeneration temperature with a purpose of utilizing low grade thermal energy. Three polymer desiccant wheels with different wheel thicknesses and different desiccant contents were tested for the dehumidification performance at various conditions of air velocity and rotation speed in a dedicated test facility placed in a climate chamber. The measured performance was compared with those of other desiccant wheels reported previously in literature. The polymer desiccant wheels were shown to display relatively higher dehumidification performance with smaller sensible temperature increase. In order to facilitate understanding the effects of the various test parameters, a single dimensionless parameter adapted from a theoretical work was introduced. It was shown that the effects of the wheel thickness, the air velocity and the rotation speed can be represented integratively by the single parameter. Similarities in the psychrometric states among the cases with different conditions were also addressed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: REGENERATION TEMPERATURE; ROTATION SPEED; PERFORMANCE; DEHUMIDIFICATION; OPTIMIZATION; PREDICT; SIMULATION; STATES; MODEL; RATES